2009
DOI: 10.1509/jmkr.46.6.754
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Response to Self-Customization Procedures: Implications for Decision Satisfaction and Choice

Abstract: Self-customization is the process by which consumers seek to customize offerings to their own preferences. In this article, the authors propose that differences in self-customization procedures potentially influence (1) the product configuration favored, (2) the degree of decision difficulty in product customization, (3) the degree of satisfaction with the customized option, and (4) the degree of willingness to purchase. The authors examine these propositions in a series of studies that allow selfcustomization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 24 publications
4
101
3
2
Order By: Relevance
“…In addition, this result can be attributed to the existence of other factors that have a stronger effect on emotion formulation, such as presentation timing, recommendation type (Ho et al 2011), or trust and anxiety (Pappas et al 2013). Our findings do not verify Valenzuela et al (2009), who found that self-customization might reduce the negative feelings that result from product customization.…”
Section: Summary Of Contributioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In addition, this result can be attributed to the existence of other factors that have a stronger effect on emotion formulation, such as presentation timing, recommendation type (Ho et al 2011), or trust and anxiety (Pappas et al 2013). Our findings do not verify Valenzuela et al (2009), who found that self-customization might reduce the negative feelings that result from product customization.…”
Section: Summary Of Contributioncontrasting
confidence: 83%
“…Penz and Hogg (2011) have found that specific types of emotions, which in general could be positive or negative, might act as mediators that influence customers' intention to purchase. Additionally, Valenzuela et al (2009) have found that negative emotions that occur from product customization weaken customers' willingness to purchase a product, but such negative emotions might be reduced with self-customization, that is "the process by which customers customize offerings to their own preferences" (p.754). When customers develop positive or negative emotions while receiving or using personalized services, they tend to give them more or less weight respectively.…”
Section: Effects Of Emotions On Purchase Intentionsmentioning
confidence: 99%
“…In contrast to such alternative-based processing, consumers who process information in attribute-based patterns aim to determine which alternative is best on each attribute. If only one attribute is important, such a lexicographic processing strategy can be useful in identifying which product to purchase (Valenzuela et al 2009). When multiple attributes are important, however, choice is typically complicated and made more difficult by the need to make trade-offs between multiple products that are superior on one attribute but not another, because buying a certain product implies that other superior features of competitive products must be sacrificed.…”
Section: Relationship Between Information Processingmentioning
confidence: 99%
“…It is also necessary to understand how this customization process works. Prior research shows that, when customizing a product, consumers need to specify their preferences as specific attribute levels (Hildebrand, Häubl, & Herrmann, 2014;Levav, Heitmann, Herrmann, & Iyengar, 2010;Valenzuela, Dhar, & Zettelmeyer, 2009).…”
Section: Introductionmentioning
confidence: 99%